Evaluating the Constructive Alignment of Learning Objectives Within Haptics Simulation in the Dental Undergraduate Curriculum - Susha Rajadurai; Tapan Hebballi; Zahra Sharif; Guneet Kaur Kukreja; Ithar Derdour (International Dental Journal)
Introduction: Simulation is increasingly becoming more common in dental curricula as an adjunct to clinical skills labs across many higher education institutions. This study seeks to explore whether the current learning objectives constructively align with our current haptics simulation curriculum – in the specific context of how well they are being met by year 1 undergraduate dental students. Method: The study incorporated a mixed methods approach to evaluate a module already taking place, which was completed from the perspectives of both the investigators and the students themselves through the triangulation of noninterventional classroom observational data, anonymous Likert-scale questionnaire data, and a literature review. Following data analysis (namely content analysis, coding systems, and descriptive statistics), the quantitative and qualitative findings were used to explore student performance in regard to each of the defined learning objectives – and subsequently related back to the current literature on ‘constructive alignment’ (CA). Results: Students were generally successful in meeting the majority of defined learning objectives, although some consistent areas of weakness were noted. These shortcomings facilitated recommendations for improvements to be formulated, which included promoting the responsibility of learning between the teachers and students. Conclusion: This study highlights that CA appears to only hold true to an extent. Numerous aspects of weakness in student performance were noted, such as troubleshooting, changing position when working on different shapes, and using indirect vision when required. CA can be enhanced in this context by promoting sharing a copy of the learning objectives with students in the session before teaching starts and using peer and individualised feedback alongside class tutorials. Clinical significance: This study aims to highlight gaps in the teaching, understanding, and CA of the learning objectives, and aims to make recommendations for their improvement. The study outlines the importance of visibility of learning outcomes to encourage learning and achieving desired outcomes.